EFFECT OF VIDEO-BASED LEARNING ON SENIOR SCHOOL STUDENTS' ACADEMIC ACHIEVEMENT IN SOLVING LINEAR EQUATION WORD PROBLEMS IN AKKO LOCAL GOVERNMENT AREA, GOMBE STATE (UNIZIK Journal of STM Education, 2025)
This research examined effect of video-based learning on senior school students'                               academic achievement in solving linear equation word problems in Akko Local Government Area, Gombe State. Two research questions and three hypotheses tested at 0.05 level of significance guided the study. The research adopted a quasi-experimental design, specifically, pre-test and post-test non-randomized control group design. In a population of 5,036 senior secondary class two students, (3,006 males and 2,030 females) in Akko Local Government Area of Gombe State, Nigeria, a sample of 70 students (40 males and 30 females) offering mathematics were selected from two out of the 16 public secondary schools in the LGA. A multistage sampling procedure was used to sample the participants namely: purposive sampling, simple random sampling and lucky dip without replacement techniques. Mathematics Achievement Test on Linear Equation Involving Word Problems (MATLEIWP) was used for data collection. Three experts validated the instruments. The reliability of the MAT was established using Kudder-Richardson 20 Formula, yielding coefficient of 0.82. The experimental and control groups were taught using researchers’ developed video model and conventional instructional strategy respectively. Mean and Standard deviation were used to answer the research questions while the hypotheses were tested using ANCOVA at 0.05 level of significance. The findings showed that, video-based learning enhanced students' achievement, gender does not have significant effect on the students’ achievement and interaction effect of method and gender was not significant on achievement in solving linear equation involving word problems. The study concludes that video based learning is effective in improving the achievement of SS 2 students in mathematics Based on the findings, it was recommended among others that; teachers should adopt video based learning strategy in teaching mathematics for improved achievement and students should also be engaged in learning using video based learning strategy on a regular basis.
Keywords: Achievement, Mathematics, SS 2 Students, Video Based Learning